Analisis Faktor Penyebab Rendahnya Minat Belajar Siswa pada Mata Pelajaran Pendidikan Kewarganegaraan Kelas XI di SMA Swasta Katolik Caritas Maumere - Mariana Boleng; Abdullah Muis Kasim; Rikardus Nasa (Riwayat: Educational Journal of History and Humanities, 2025)
The problem in this study is that many students are still outside the school environment when the lesson starts; they are busy talking with their classmates, always asking permission to leave the class during the teaching and learning process, which greatly disrupts the continuity of the teaching and learning process. Interest in learning arises from students' willingness, attention, and activeness, which makes them enjoy the learning process and develop in knowledge, attitudes, and skills. Citizenship education aims to form good citizens, namely individuals who understand, care about, and are aware of their rights and responsibilities. This study aims to determine the causes of low student interest in Civics Education class XI at Caritas Maumere Catholic Private High School and the efforts made to overcome it. The research used qualitative methods with observation, interview, and documentation techniques and data analysis through reduction, presentation, and conclusion drawing. Data sources came from students and teachers. The results showed that low interest in learning was caused by internal factors, such as health problems, lack of motivation, lack of focus, and low motivation.